2012
DOI: 10.4081/jlimnol.2012.e32
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a catastrophic storm event on benthic macroinvertebrate communities in upland headwater streams and potential implications for ecological diversity and assessment of ecological status

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…However, we emphasize, that the demonstrated increase in hyporheic reactive efficiency with increasing stream discharge will not be unlimited. Very intense and destructive stream discharge events with increasing turbidity and sediment mobilization may disturb the entire aquatic ecosystems and its reactivity [e.g., Resh et al ., ; Feeley et al ., ; Löfgren et al ., ]. Most likely, such events will induce a temporal decline in reaction efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we emphasize, that the demonstrated increase in hyporheic reactive efficiency with increasing stream discharge will not be unlimited. Very intense and destructive stream discharge events with increasing turbidity and sediment mobilization may disturb the entire aquatic ecosystems and its reactivity [e.g., Resh et al ., ; Feeley et al ., ; Löfgren et al ., ]. Most likely, such events will induce a temporal decline in reaction efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Beside natural flood events, human dam operations leading to downstream stream stage oscillations have an impact on stream‐groundwater systems [ Arntzen et al ., ; Sawyer et al ., ; Casas‐Mulet et al ., ]. Furthermore, the perturbations caused by flood events are relevant for microbial communities [ Holmes et al ., ] and invertebrates [ Olsen and Townsend , ; Feeley et al ., ] and to some degree are needed for a good functioning of the aquatic ecosystem [ Resh et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The five extreme high‐rainfall events included here all resulted in flash flooding and/or a rapid increase in bankfull discharge in the Glenfinish River, accompanied by large‐scale scouring of the riverbed and upheaval and entrainment of in‐stream substrata (Twomey & Giller, ). Comparable amounts of 24‐h rainfall resulted in similarly high levels of disturbance in other Irish running waters; hence, these events can be considered as extreme for the general locale (Feeley et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Because extreme events are by definition rare, and often unpredictable, capturing them in natural systems is largely fortuitous (e.g. Fisher et al ., ; Lamberti et al ., ; Covich, Crowl & Heartsill‐Scalley, ; Feeley et al ., ). Furthermore, extreme climatic events (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…A clear distinction in the richness and diversity in the aquatic invertebrate community has also been found between dry and rainy periods. For example, Rios-Touma et al (2011) observed a higher richness and diversity of the aquatic invertebrate community during the dry season in the Piburja stream (Ecuador), and Feeley et al (2012) noted that high water levels due to increased rainfall induced significant losses in the richness and diversity of the invertebrate community. However, some studies have demonstrated that responses in invertebrate communities are probably not directly coupled to precipitation, but occur via related changes in stream characteristics, such as the carriage of sediments and organisms, due to an increase in current velocity and water flow (Oliveira et al 1997).…”
Section: Introductionmentioning
confidence: 99%